Life Course Trajectories for Young Pasifika in Aotearoa: Protocol for the 25-year Follow-up of the Pacific Islands Families Study Cohort - Tautolo, El-Shadan; Bakir-Demir, Tugce; Jalili-Moghaddam, Shabnam; Savila, Faasisila; Kokaua, Jesse; Schluter, Philip J; Ofe-Grant, Maulupeivao Betty; Rush, Elaine; Mohammed, Jalal; Vaka, Sione; Tiatia-Siau, Jemaima; Cammock, Radilaite; et al. (JMIR Publications, 2025)
BACKGROUND: From birth, many young Pacific people in Aotearoa New Zealand experience a disproportionately high burden of psychological distress, metabolic disease, and socioeconomic disparities within education and employment which contribute to significant health inequalities. Further research is needed to understand the drivers influencing these outcomes. OBJECTIVE: This paper provides a comprehensive overview of the quantitative component of the Pacific Island Families Study: Ala mo Tupulaga Pasifika Aotearoa (PIF:ATP; Life Course Trajectories for Young Pasifika in Aotearoa), the latest follow-up of the longitudinal PIF birth cohort study, which uses a mixed-methods approach. METHODS: The PIF Study is a multidisciplinary longitudinal study that tracks the health and development of 1398 Pacific children born in 2000 at Middlemore Hospital, South Auckland, Aotearoa, New Zealand. Data collection has occurred at 10 time points from infancy through young adulthood, with this PIF:ATP assessment phase occurring at ages 25-26 years, which aims to reach at least 750 cohort members. The assessments will take place at participants' homes or at Auckland University of Technology for those residing in Auckland. Data collection will be conducted across multiple sites, including Auckland, Wellington, Hamilton, and Whangārei in Aotearoa New Zealand, as well as Brisbane, Sydney, and Melbourne in Australia. Physical measurements such as weight, height, waist and hip circumferences, grip strength, body fat mass and muscle mass, blood pressure and pulse, glucose and lipid screening, and skin carotenoid concentration will be undertaken. In addition, self-reported data will be collected on psychological well-being (eg, depression, anxiety, and family functioning), nutritional and metabolic well-being (eg, food intake and physical activity), and economic well-being (eg, educational attainment, employment status, and job occupation and industry). RESULTS: Data collection is scheduled to commence in June 2025 and conclude by December 2026. The first set of results and analysis is expected to be published from December 2027 onward. Reporting of all results will comply with the Strengthening the Reporting of Observational studies in Epidemiology (STROBE) guidelines. CONCLUSIONS: This paper presents the protocol for the 25-year follow-up of the first Pacific longitudinal cohort study, which will comprehensively examine psychological, nutritional, metabolic, and economic well-being of Pacific young adults. With 25 years of longitudinal data and extensive expertise in life course research, this protocol outlines the design, methodology, and scope of the quantitative component of the PIF:ATP research program. This phase is uniquely positioned to address key issues identified by Pacific communities and generate evidence to inform meaningful interventions and guide policy development while providing robust, contemporary, high-quality empirical evidence.
Keywords: determinants of health; economic wellbeing; life course epidemiology; longitudinal research; nutritional and metabolic wellbeing; pacific youth health; protocol; psychological wellbeing; 4206 Public Health; 42 Health Sciences; Obesity; Women's Health; Health Disparities; Clinical Research; Mental Health; Health Disparities and Racial or Ethnic Minority Health Research; Nutrition; Pediatric Research Initiative; Minority Health; Prevention; Behavioral and Social Science; 2.3 Psychological, social and economic factors; 1103 Clinical Sciences; 1117 Public Health and Health Services; 4203 Health services and systems; 4206 Public health; Adolescent; Adult; Child; Child, Preschool; Female; Humans; Infant; Male; Young Adult; Cohort Studies; Follow-Up Studies; Longitudinal Studies; New Zealand; Pacific Islands; Pacific Island People; Population Health; Humans; Cohort Studies; Longitudinal Studies; Follow-Up Studies; Adolescent; Adult; Child; Child, Preschool; Infant; New Zealand; Pacific Islands; Female; Male; Young Adult; Population Health; Pacific Island People; Adolescent; Adult; Child; Child, Preschool; Female; Humans; Infant; Male; Young Adult; Cohort Studies; Follow-Up Studies; Longitudinal Studies; New Zealand; Pacific Islands; Pacific Island People; Population Health